PEMBELAJARAN BAHASA BERBASIS KURIKULUM 2013 DI PAUD ASPARAGA MALANG - Erfan Mokhamad Wijaya (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2017)
This classroom-based observation qualitative study describes language learning process in the kindergarten level based on the 2013 Curriculum. This study took place in the Kindergarten of Asparaga Malang and assigned all pupils as the research subject.  Data of this study were obtained form classroom interactions in the Asparaga school using observation and interview. This study revealed that the pupils in Asparaga interacted with friends and teachers in four languages: (1) Javanese language, (2) Indonesian, (3) the English language, and (4) Arabic. Learning a language was considered interesting using of various methods: teachers applied the storytelling and play to teach the languages, and multiple medias to support language learning process were also used in support to use the books, pictures, and tablets.